Assessing the Attitudes and Clinical Practices of Ohio Dentists Treating Patients with Dental Anxiety - Kristin A. Williams; Sarah Lambaria; Sara Askounes (MDPI AG, 2016)
Dental anxiety (DA) negatively affects patients' oral and overall health. This study explored attitudes and clinical practices of licensed Ohio general dentists who treat patients with DA. Methods: An anonymous self-administered mail survey was sent to 500 general dentists licensed and practicing in Ohio. Responses to 21 pre-coded questions were analyzed. Frequencies were examined; cross-tabs, Chi-Square, and Fischer's Exact Test were calculated for statements according to dentists' gender. Alpha was set at p = 0.05. Results: Nearly all respondents treated anxious patients; males were more likely to find it challenging than females. Dentists were most familiar with distraction, although half found nitrous oxide to be an effective tool. Female dentists were more likely than males to be familiar with anxiolytics and find them effective. Conclusion: Overall, Ohio general dentists are most familiar with using distraction and nitrous oxide during appointments for anxious patients. Gender differences exist in attitudes towards anxiolytic use for patients with DA. Practice Implications: By identifying techniques that are comfortable for patient and practitioner, oral health disparities associated with DA may be reduced.